Glucosinolate Content in Dormant and Germinating Arabidopsis thaliana Seeds Is Affected by Non-Functional Alleles of Classical Myrosinase and Nitrile-Specifier Protein Genes - Meier, Kathrin; Ehbrecht, Markus D.; Wittstock, Ute (Frontiers in Plant Science, 2019)
While the defensive function of glucosinolates is well established, their possible role as a nutrient reservoir is poorly understood and glucosinolate turnover pathways have not been elucidated. Previous research showed that glucosinolate content in germinating seeds of Arabidopsis thaliana Columbia-0 (Col-0) increases within the first two to four days on culture medium and then decreases below the level at day 0. In this study we used previously characterized T-DNA mutants to investigate if enzymes known to be involved in glucosinolate breakdown upon tissue damage affect the time course of glucosinolate content in germinating seeds. Besides dormant seeds, we analyzed seeds subjected to stratification in water for up to 72 h or germination on plates for up to ten days. Although seeds of tgg1 tgg2 (deficient in above-ground classical myrosinases) had higher glucosinolate levels than Col-0, the changes during germination were not different to those in seeds of Col-0. This demonstrates that TGG1/TGG2 are not responsible for the decline in glucosinolate content upon germination and suggests the involvement of other enzymes. Expression data extracted from publically available databases show a number of β-glucosidases of the BGLU18-BGLU33 clade to be expressed at specific time points of seed maturation and germination identifying them as good candidates for a role in glucosinolate turnover. Although nitrile-specifier proteins (NSPs) act downstream of myrosinases upon glucosinolate breakdown in tissue homogenates, mutants deficient in either seed-expressed NSP2 or seedling-expressed NSP1 were affected in glucosinolate content in seeds and during stratification or germination when compared to Col-0 indicating a direct role in turnover. The mutant lines nsp1-1, nsp2-1 and nsp2-2 had significantly higher glucosinolate levels in dry seeds than Col-0. After 24 h of stratification in water, nsp2 2 seeds contained 2.3fold higher levels of glucosinolate than Col-0 seeds. This might indicate downregulation of hydrolytic enzymes when nitrile formation following glucosinolate hydrolysis is impaired. The time course of total glucosinolate content during ten days of germination depended on functional NSP1. Based on the present data, we propose a number of experiments that might aid in establishing the pathway(s) of glucosinolate turnover in germinating A. thaliana seeds.